Biochemical Investigations into Anticoagulants In Salivary Glands Of The Tick Ornithodoros Sa Vignyi Audouin (1827) - Neitz, A.W.H. (Albert Walter Herman) (University of Pretoria, 2022)
Thesis (PhD)--University of Pretoria, 1995.